Hydrogenase biomimetics with redox-active ligands: Electrocatalytic proton reduction by [Fe2(CO)4(κ2-diamine)(μ-edt)] (diamine = 2, 2′-bipy, 1, 10-phen). (25th September 2016) - Ghosh, Shishir; Rahaman, Ahibur; Holt, Katherine B.; Nordlander, Ebbe; Richmond, Michael G.; Kabir, Shariff E.; Hogarth, Graeme
Graphical abstract: Diiron complexes bearing redox active diamine ligands have been studied as models of the active site of [FeFe]-hydrogenases. Electrochemical experiments and DFT calculations are used to try and understand the interplay between metal and ligand redox sites. Abstract: Diiron complexes bearing redox active diamine ligands have been studied as models of the active site of [FeFe]-hydrogenases. Heating [Fe2 (CO)6 (μ-edt)] (edt = 1, 2-ethanedithiolate) with 2, 2′-bipyridine (2, 2′-bipy) or 1, 10-phenanthroline (1, 10-phen) in MeCN in the presence of Me3 NO leads to the formation of [Fe2 (CO)4 (κ 2 -2, 2′-bipy)(μ-edt)] (1-edt ) and [Fe2 (CO)4 (κ 2 -1, 10-phen)(μ-edt)] (2-edt ), respectively, in moderate yields. In the solid state the diamine resides in dibasal sites, while both dibasal and apical–basal isomers are present in solution. Both stereoisomers protonate readily upon addition of strong acids. Cyclic voltammetry in MeCN shows that both complexes undergo irreversible oxidation and reduction, proposed to be a one- and two-electron process, respectively. The structures of neutral2-edt and its corresponding one- and two-electron reduced species have been investigated by DFT calculations. In2-edt − the added electron occupies a predominantly ligand-based orbital, and the iron–iron bond is maintained, being only slightly elongated. Addition of the second electron affords an open-shell triplet dianion where the second electron populates an Fe–Fe σ * antibonding orbital, resulting in effective scission of the iron–iron bond. The triplet state lies 4.2 kcal mol −1 lower in energy than the closed-shell singlet dianion whose HOMO correlates nicely with the LUMO of the neutral species2-edt . Electrocatalytic proton reduction by both complexes has been studied in MeCN using CF3 CO2 H as the proton source. These catalysis studies reveal that while at high acid concentrations the active catalytic species is [Fe2 (CO)4 (μ-H)(κ 2 -diamine)(μ-edt)] +, at low acid concentrations the two complexes follow different catalytic mechanisms being associated with differences in their relative rates of protonation.